The selective FKBP51 inhibitor SAFit2 reduces alcohol consumption and reinstatement of conditioned alcohol effects in mice - König, Loretta; Kalinichenko, Liubov; Huber, Sabine; Voll, Andreas M.; Bauder, Michael; Kornhuber, Johannes; Hausch, Felix; Müller, Christian P. (Addiction Biology, 2019)
There is still no widely effective pharmacotherapy for alcohol addiction available in the clinic. FK506-binding protein 51 (FKBP51) is a negative regulator of the glucocorticoid receptor signaling pathway that regulates the stress-induced glucocorticoid feedback circuit. Here we asked whether selective inhibitors of FKBP51, exemplified by SAFit2, may serve as a new pharmacological strategy to reduce alcohol consumption and conditioned alcohol effects in a mouse model. We report that a relatively short treatment with SAFit2 (20 mg/kg, ip) reduces ongoing 16 vol% alcohol consumption when administered during free access to alcohol in a two-bottle free-choice test. SAFit2 was also able to reduce alcohol consumption when given during an abstinence period immediately before relapse. In contrast, SAFit2 did not affect alcohol consumption when given during a relapse period after repeated withdrawal from alcohol. SAFit2 (10 and 20 mg/kg, ip) showed no effects when used in an intermittent drinking schedule. When 20 vol% alcohol was only available every other day, SAFit2 had no effect on drinking, no matter whether given during a drinking episode or the day before. SAFit2 (2 and 20 mg/kg, ip) did not affect the expression of an alcohol-induced conditioned place preference (CPP). However, SAFit2 was able to inhibit alcohol-induced reinstatement of an extinguished CPP in a dose-dependent way. Altogether, these data may suggest pharmacological inhibition of FKBP51 as a viable strategy to reduce alcohol seeking and consumption.
CRIS-Team Scopus Importer:2019-06-25
Keywords: alcohol; conditioned place preference; drinking; FKBP51; SAFit2